2020
DOI: 10.1121/10.0001184
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the tonal sound generation during phonation with and without glottis closure

Abstract: The human phonation is characterized by periodical oscillations of the vocal folds with a complete glottis closure. In contrast, a glottal insufficiency (GI) represents an oscillation without glottis closure resulting in a breathy and weak voice. In this study, flow-induced oscillations of silicone vocal folds were modeled with and without glottis closure. The measurements comprised the flow pressure in the model, the generated sound, and the high-speed footage of the vocal fold motion. The analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…Furthermore, the qualitative trend of CPP was also found in ex vivo studies with human (Birk et al, 2017b) and rabbit larynges (Döllinger et al, 2018;Thornton et al, 2019), as shown in Table 4. The high CPP values for GC2 and GC3 for symmetrically oscillating VFs shows, that the acoustic signal is still tonal and physiological for small posterior gaps as often observed in physiological phonation of women and childs (Södersten and Lindestad, 1990;Södersten et al, 1995;Inwald et al, 2010;Patel et al, 2012;Kniesburges et al, 2020). Quantitatively, our CPP values are in the range of values reported by Döllinger et al (2018) and Thornton et al (2019).…”
Section: Quality Of Acoustic Signalsupporting
confidence: 67%
See 4 more Smart Citations
“…Furthermore, the qualitative trend of CPP was also found in ex vivo studies with human (Birk et al, 2017b) and rabbit larynges (Döllinger et al, 2018;Thornton et al, 2019), as shown in Table 4. The high CPP values for GC2 and GC3 for symmetrically oscillating VFs shows, that the acoustic signal is still tonal and physiological for small posterior gaps as often observed in physiological phonation of women and childs (Södersten and Lindestad, 1990;Södersten et al, 1995;Inwald et al, 2010;Patel et al, 2012;Kniesburges et al, 2020). Quantitatively, our CPP values are in the range of values reported by Döllinger et al (2018) and Thornton et al (2019).…”
Section: Quality Of Acoustic Signalsupporting
confidence: 67%
“…For GC4 and GC5, the vocal folds remain open along the entire glottis length during the oscillation cycle, see Supplementary Videos 3, 4. This absent interruption of the glottal jet is often related to an aspirated voice signal characterized by lower tonal sound components (Fritzen et al, 1986;Bhatt and Verma, 2014;Kniesburges et al, 2020). As reported by Sadeghi et al (2018), the VeFs have a stabilizing influence on the glottal jet.…”
Section: Energy Transfermentioning
confidence: 82%
See 3 more Smart Citations